Urban road feature database and route planner for an autonomous vehicle - Antony Raj Antony Prince (2008)
The objective of this dissertation is to study and implement the task of path planning. Digital map data is needed for implementation, the first step is to represent Nanyang Technological University (NTU) in a digital representation. Secondly, implement the shortest path algorithms, i.e Dijkstra’s and A* algorithm with respect to the NTU map for route guidance systems.